2021
DOI: 10.3390/ijms221910866
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Mitochondrial Mechanism in NLRP3 Inflammasome Activation and Exercise Regulation of NLRP3 Inflammasome

Abstract: NLRP3 is an important pattern recognition receptor in the innate immune system, and its activation induces a large number of pro-inflammatory cytokines, IL-1β and IL-18 which are involved in the development of various diseases. In recent years, it has been suggested that mitochondria are the platform for NLRP3 inflammasome activation. Additionally, exercise is considered as an important intervention strategy to mediate the innate immune responses. Generally, chronic moderate-intensity endurance training, resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 97 publications
0
16
0
Order By: Relevance
“…The major aim of this study was to investigate the effect of Dex through NLRP3 signaling on a POCD model. ROS generation partly depends on the activation of NLRP3 inflammasomes [ 43 , 44 , 45 ]. We could not confirm the effect of DEX on ROS regulation in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major aim of this study was to investigate the effect of Dex through NLRP3 signaling on a POCD model. ROS generation partly depends on the activation of NLRP3 inflammasomes [ 43 , 44 , 45 ]. We could not confirm the effect of DEX on ROS regulation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has also been proposed as the possible cause for neurodegenerative and neurocognitive diseases leading to POCD and delirium [ 46 ]. It has been reported that mitochondrial oxidative stress is one of the crucial factors involved in NLRP3 inflammasome activation [ 44 ]. It is worth investigating whether the protective effect of Dex through the NLRP3 inflammasome pathway is also related to the regulation of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that ROS, produced by the respiratory chain, activate the NLRP3 inflammasome, which is a known activator of excessive inflammatory responses. Under physiologic conditions there is only a low leakage of ROS, but damage to the respiratory chain produces higher amounts of ROS and stronger activation of the NLRP3 inflammasome [ 64 ]. Since it is not known, if there is an increased production of ROS within the given samples, this is only speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, eugenol supplementation along with aerobic exercise is likely to control neuronal damage caused by diabetes [ 33 ]. It is likely that the mechanisms to explain the effects of endurance training on inflammatory factors can be attributed to the regulation of mTROS production with mitochondrial quality control (mitochondrial proliferation and mitochondrial activation), improvement of mitochondrial function, and increase in cleansing of damaged mitochondria, and hence, it can inhibit the NLRP3 inflammasome pathway and prevent extreme inflammatory reactions [ 34 ]. The nerve tissue has a frail antioxidant system, which due to high oxygen consumption is exposed to oxidative injuries; on the other hand, oxidative stress is the common pathway of cell damage as a result of hyperglycemia [ 35 ].…”
Section: Discussionmentioning
confidence: 99%